Influence of Plant Growth Promoting Rhizobacteria (PGPR) on the Productivity of Pelargonium graveolens L. Herit - Mansoor Alam2; Anupam Dikshit1*, Rohit Kumar Mishra1, Om Prakash2 (Recent Research in Science and Technology, 2010)
In the revival of herbal age, aromatic crops are being commercially cultivated in order to fetch the great demand of essential oils used by food, pharmaceutical flavour, perfumery and cosmetics industries. Two isolates of plant growth promoting rhizobacteria (PGPR) which were isolated from the rhizosphere soil of Pyrethrum (Chrysanthemum cineraefolium) designated as MA-2 and MA-4, and identified as Bacillus subtilis and Pseudomonas fluorescens on the basis of cultural as well as biochemical testing. They gave excellent result on the productivity of Pelargonium graveolens, increased herb yield over control by 9 and 27.6% respectively.